Mini skein knits : 25 knitting patterns using small skeins and leftovers. (Lark, 2015)
"Mini skeins are the hottest new trend in the fiber world and this collection of 25 knitting patterns will give you plenty of ideas on how to creatively use these tiny collectible skeins. Create 25 beautiful patterns that range from a woman's striped crewneck pullover and cardigan to a slouchy beanie and a trio of matching winter accessories to a hanging kitchen towel and coffee cup cozy. This is also the perfect pattern collection for using up leftover yarn. Mixing and matching mini skeins with yarn leftovers will make a colorful and budget-savvy new project,"--Amazon.com.